Adjustment problem and associated factors among first-year undergraduates at Wollo University, Ethiopia - Anbesaw, Tamrat; Beyene, Abeba; Kefale, Jerusalem (Frontiers in Education, 2022)
Abstract Background: Adjustment problems are characterized by a maladaptive emotional response to a stressful event among first-year fresh students. In Ethiopia, there is limited evidence about the adjustment problem and its determinant factors among undergraduate students. So, the present study aimed to assess the prevalence of adjustment problem and associated factors among first-year undergraduate students at Wollo University, Dessie, Ethiopia. Methods: Institutional-based cross-sectional study design was conducted from February 1-20/2020. A systematic random sampling technique was employed to select the study participants. The result adjustment problem was assessed using the Student Adjustment to College Questionnaire (SACQ). Data were analyzed using SPSS version 26. Logistic regression analysis was performed and variables with a p-value less than 0.05 were taken as statistically significant with adjustment problem. Results: The prevalence of adjustment problem among first-year undergraduate students was found to be 41.4% (95% CI (35.8, 46.9). Those students' hometowns far > 901 km from the university, monthly pocket money < 1000 ETB, away from family/home for the first time, and facing great difficulty in living in a dormitory were significantly associated with adjustment problem among university students. Conclusion: The prevalence of adjustment problem among Wollo university students was high and positively associated with students home town far > 901 km from the university, monthly pocket money, being away from family/home for the first time, and facing great difficulty in living in a dormitory. Therefore, establishing adjustment problem screening services on the campus and designing proper mental health intervention programs are recommended to tackle the problem.